Addressing Fire Safety, Ground Impact Resistance, and Thermal Management in Composite EV Battery Enclosures: A Review - Sunarto Kaleg; Danardono Agus Sumarsono; Yudan Whulanza; Alexander Christantho Budiman (Universitas Muhammadiyah Magelang, 2024)
Lithium-ion batteries are fundamental to modern electric vehicles, offering high energy density, long cycle life, and low self-discharge rates. However, thermal runaway—a critical safety issue involving uncontrolled temperature increases—can lead to fire or explosion. Ensuring flame retardancy is crucial in accidents where battery packs are exposed to external fires. Additionally, battery packs are susceptible to mechanical stresses and potential damage from ground impacts like debris or uneven road surfaces. Effective thermal management significantly impacts capacity and longevity. This review emphasizes the importance of researching flame retardancy, ground impact resistance, and thermal management, especially in composite battery enclosures. Composites serve as a lightweight alternative to metals and help overcome one of the main constraints of EVs, which is weight. Ground impact refers to the physical force battery packs endure during collisions, hitting potholes, debris, or accidents. Therefore, understanding the effects of ground impact on battery enclosures is crucial for design considerations. Effective thermal management is also essential, as it directly affects the performance and safety of Lithium-ion battery packs in EVs.